(untitled) (El Hilo de la Fabula, 2010)
It is analised the rehabilitation that Martha Nussbaum carries out from the pair ethics-literature. It is studied the way in which the philosophic project of the author qualifies an aristotelic conception of moral philosophy as a search of the good life. It enquieres into the way in which this author conceibes the relation ethics and literature and the philosophical arguments that presents to make it intelligible. Are presented the vinculums that share with ethical critics of Wayne Booth. Are presented the problems which are supoused to appeal to the emotions as guides to the public practice, with special referencies to the problem of love.